A New Design of Capacitive Power Transfer Based on Hybrid Approach for Biomedical Implantable Device - Zaki Mustapa; Shakir Saat; Yusmarnita Yusof (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper presents the development of a new design method of capacitive power transfer (CPT) which is based on hybrid concept for Biomedical Implants. This method is able to improve various issues found in the widely used CPT system that is bipolar CPT method. Based on the ability of this purposed, the simulation of the CPT system has been designed to prove an amount of power transferred through a layer of tissue. The design used to validate the suggested model which to powering implanted device, and it was performed with 3cm square plates, which have a layer of beef with the 5mm thickness in between 2 coupling plate. Power signal was generated by Class E zero voltage switching. The Class E zero voltage switching has been designed to generating alternate current with the 1MHz frequency appropriate to the hybrid CPT system specification.